Insights into Classic Theatre Market Segments - Leko Šimić Mirna; Pap Ana (Naše gospodarstvo/Our economy, 2020)
Marketing segmentation is one of the key strategic elements in marketing plan- ning that helps identifying key consumer groups and their characteristics and enables the adaptation of marketing strategies to different target consumers. The aim of this paper is paper aims to segment classic theatre audiences based on their attendance frequency and identify major socio-demographic charac- teristics of each segment. A self-completion questionnaire was developed upon analysis of previous studies and was distributed to the population in an area of about 50 km around Osijek. The research was conducted on a convenient sample, using an in-person method in two different intervals: in the first inter- val, research was conducted on young respondents (18-34), and in the second interval, research was conducted on adult respondents (age 35+). Altogether 1315 participants took part in the research. Statistical techniques of univariate analysis (frequency distribution and central tendency measures), ANOVA, and two-step cluster analysis were used. The results of the study have identified six classic theatre segments: young the- atre friends, young theatre acquaintances, young theatre strangers, adult theatre friends, adult theatre acquaintances, adult theatre strangers. Each segment is described in detail by their geographic (distance from the venue), demographic (age, income, marital status, education, employment) and psychographic char- acteristics (social activities, free time spending, and informing gathering about classic theatre offer) characteristics. The research results emphasized the differ- ences in classic theatre audiences, which calls for continuous market segmen- tation in order to ensure timely recognition of consumer trends and changes in preferences. This would enable theatre management to adapt and implement adequate marketing initiatives and strategies.